Impact of the Development of Aquaculture on Income and Employment in Sub District of Airtiris Kampar District Riau Province - Nurul Santri; Firman Nugroho; Kusai Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRAKThis research was conducted in January 2017 which is located in sub district of Airtiris Kampar regency of Riau Province. This study aims to determine the development of aquaculture as well as to determine the impact of the development of aquaculture to the income of society and employment in the urban village. The method used in this study is a Survey with the number of respondents as many as 63 people.Aquaculture in Airtiris there are two is one aquaculture in Karamba and aquaculture in pond, aquaculture in karamba every year has increased seen from the increasing number of karamba units, while aquaculture in pond decreased due to reduced land due to the constructions of building and housing. The development of aquaculture provides an opportunity for the society to create new business venture related to aquaculture. Such as the business of making karamba, pellet making business, pellet selling business, fish seed supplying business, land leasing business and food sales business around the river, thereby increasing the income of society and can reduce unemployment rate. Key Word : Aquaculture, Income, Employment.